Advantages and barriers of university-business linkages: Analysis from an academic perspective - Mueller, Adilson (2025)
This article addresses university-business linkages to promote innovation, examining the advantages, barriers and strategic actions observed by researchers and professors from Latin American academic institutions. To carry out the analysis, an online survey was applied to a sample of 305 participants residing in different Latin American countries, that is: Brazil, Panama, Colombia, Costa Rica, Bolivia, Ecuador, and Mexico. The core results reveal 15clear advantages of university-business linkages, including the transfer of research results and greater visibility for universities and their research groups. The main barriers emerging from the analysis, including financing problems, lack of human resources and lack of time management, varied by country, gender and age ofparticipants. The findings of the study provide guidance for strategic actions to strengthen university-business links in Latin America, highlighting the importance of adaptability and adaptation to changing environmental conditions in order to better exploit the mutual collaborative benefits of innovation and sustainable development.